Ritchie's Fabulae Faciles: A First Latin Reader - Ritchie, Francis; Kirtland, John Copeland, 1870-1951 (Salt Lake City, UT : Project Gutenberg, 2005)
"Ritchie's Fabulae Faciles: A First Latin Reader" by Francis Ritchie is a language educational text likely written in the early 20th century. It serves as an introductory guide for students learning Latin, featuring simplified retellings of classical myths and stories to ease beginners into the complexities of the Latin language and narrative. The beginning of the reader features a preface by John Copeland Kirtland, Jr., who outlines the educational purpose behind the collection of Latin fables. Kirtland explains that these stories were initially presented to him by a colleague, and he found them highly effective for teaching novices in Latin due to their engaging narratives and gradually increasing difficulty levels. The opening sets the stage for the stories to follow, specifically focusing on the myth of Perseus, detailing his origins, struggles, and eventual triumphs, introducing key characters and themes that illustrate the valor and adventures typical in classic mythology. This structured approach is intended to captivate young learners while building their confidence in reading Latin through contextually relevant and culturally significant tales. (This is an automatically generated summary.)
Release date is 2005-09-01
Produced by Karl Hagen, Tapio Riikonen and Online Distributed Proofreaders
Keywords: Latin language -- Readers -- Mythology